Estudo comparativo do indice de GINI de Minas Gerais entre os anos de 1990 a 2010 via Krigagem Ordinaria e Krigagem Particao - Abreu, Reinaldo Junio Dias de; Almeida, Maria de Fatima F.; Duraes, Gustavo Rafael Nunes; Govone, Jose Silvio [UNESP] (Univ Federal Alfenas, 2023)
The GINI index is a measure of inequality widely used to verify the income distribution of a region, it indicates the difference in income from the poorest to the richest, and varies numerically between values from 0 to 1, where the highest value indicates large concentration of income. Performing the analysis of this index in the State of Minas Gerais, using data from Atlas IBGE from 1991 to 2010, it was possible to build maps of Ordinary Kriging and Split Kriging using the Spatial Product Partition Model (SPPM). With the Split Kriging, a division in the sampling grid of the state was obtained, which showed the separation of the central region, the most economically developed in the state, in the 3 analysed periods, and the fluctuation of the GINI indices over the periods in the other regions. We conclude that there was a gradual increase in the GINI index in practically most of the mesoregions of the North of Minas, and the West of Minas remained with the lowest index during all periods compared to the other regions.
Keywords: GINI Index; Ordinary Kriging; Split Kriging; Product Partition Model